URBAN MINING BATERAI LITHIUM BEKAS SEBAGAI SUMBER ALTERNATIF BAHAN BAKU BATERAI LITHIUM - Puspita, Daniel Fajar; Deni Cahyadi (LPPM Universitas Terbuka, 2022)
An urban mining proposal has been made that offers a lithium battery waste managementsolution. This is motivated by the absence of a waste management system that specificallyhandles lithium batteries. The research was conducted quantitatively for electrochemicaldischarge experiments and qualitatively for data collection, processing and formulation of urbanmining proposals. From the experimental results, it was found that 5% NaCl is the optimumconcentration for electrochemical discharge. Obstacles are still found based on qualitativeanalysis of waste management data in Indonesia, especially for lithium battery waste. The scopeof the proposed urban mining system includes the people as the user and the temporarycollectors. Hopefully this urban mining design is beneficial for an effective and environmentallyfriendly lithium battery waste management plan.